The political economy of energy innovation - Shouro Dasgupta; Enrica De Cian; Elena Verdolini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper empirically investigates the effects of environmental policy, institutions, political orientation, and lobbying on energy innovation and finds that they significantly affect the incentives to innovate and create cleaner energy efficient technologies. We conclude that political economy factors may act as barriers even in the presence of stringent environmental policy, implying that, to move towards a greener economy, countries should combine environmental policy with a general strengthening of institutional quality, consider the influence of government's political orientation on environmental policies, and the implications of the size of energy intensive sectors in the economy.
Keywords: C23; D02; O30; Q58; 330; energy innovation; environmental policy; patents; political economy